MEDICINAL RESEARCH ON BRITISH PLANTS - Simmonds, Monique S. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Many British plants are used in herbal medicines and some provided leads for pharmaceuticals. However, in the last 40-50 years natural- product researchers in Britain has had a tendency to work on more exotic species from Africa, Asia and South America. Since the late 1990s researchers at Kew are involved in two key projects that have an emphasis on medicinal properties of British plants. The first project involves investigating the traditional uses of the plants and will provide chemical data that that could be valuable in the quality control of plant material being used. The other is a project called Ethnomedica or “remembered remedies” that concentrates on collating information about the medicinal uses of plants in UK between 1900 and 1948. This is just before the start of the National Health Service. Both projects are very collaborative. The Ethnomedica project involves herbalists, the Natural History Museum, Eden Project, Chelsea Physic Garden and students from different universities, including, Kent and Edinburgh that have been helping to gather information. The talk will give a summary of both projects especially those with wound healing, anti-microbial and anti-oxidant activity and those that contain compounds that have potential for use in studying Alzheimer, cancer and cardiovascular diseases. It will also provide an overview of the links between the traditional use data gathered via the Ethnomedica project and research into the chemistry of the different species.